Komposisi dan Struktur Strata Sapling di Kawasan Geopark Silokek Kabupaten Sijunjung - Savira Geovana; Chairul Chairul (Bioscientist : Jurnal Ilmiah Biologi, 2023)
This study aims to determine the composition and structure of the sapling strata of plants in the Silokek Geopark Area, Sijunjung Regency. Vegetation analysis was carried out using the transect method with a plot size of 5 x 5 m. 10 plots were made and the identification of unknown plant species was carried out at the Andalas University Herbarium. Based on the research results found 31 species consisting of 48 individuals with 14 families. The co-dominant families are Euphorbiaceae, Annonaceae, Leguminosae, and Sapindaceae. The highest important value index is Archidendron bubalinum. The diversity index of the sapling strata vegetation in this area is high (H' = 3.28). Based on the research, it can be concluded that the Euphorbiaceae, Annonaceae, Leguminosae, and Sapindaceae families support the composition and structure of the vegetation in the area.